Best self be you, only better - Bayer, Mike (New York Dey St., an imprint of William Morrow, 2019)
"Think about your daily life. Are you thriving, or going through the motions? Are your days full of work, relationships, and activities that are true to your authentic self, or do you feel trapped on a treadmill of responsibility? If you dream of a better life, now is the time to turn your dream into reality. And the tools you need are within your grasp. Mike Bayer, known to the thousands of clients whose lives he has changed as Coach Mike, has helped everyone from pop stars to business executives to people just like you discover the freedom to be their best selves. By asking them and leading them to ask themselves a series of important but tough questions -- such as "What are your core values?" "Do you go to bed each day more knowledgeable than when you woke up?" and "Am I neglecting some aspect of my physical health out of fear or denial?"--He helps them see what their Best Selves and Anti-Selves really look like. As a mental health specialist, a personal development coach, and an all-around change agent, Mike has seen the amazing ways in which lives can improve with honesty and clarity. He understands our struggles intimately, because he's faced -- and overcome -- his own. By working through each of the Seven SPHERES of life -- Social, Personal, Health, Education, Relationships, Employment and Spiritual Development -- Best Self is an interactive book that distills all of Coach Mike's wisdom into a compact, focused guide that will ignite anyone's desire for change. Chock full of revealing quizzes and provocative questionnaires, Best Self will empower you to embrace your authenticity, acknowledge what is holding you back, and break through to live a passionate life to the fullest, forever."--Publisher's description
Foreword / Dr. Phil McGraw -- Discovering your best self -- Understanding your anti-self -- Your unique journey: The best self tenets of change -- Identifying your obstacles -- The Spheres: Your social life -- The sPheres: Your personal life -- The spHeres: Your health -- The sphEres: Your education -- The spheRes: Your relationships -- The spherEs: Your employment -- The sphereS: Your spiritual development life -- Assembling your best team -- Seven steps for acquiring your best self goals -- Conclusion
Includes bibliographical references
1
Keywords: FAMILY & RELATIONSHIPS -- Love & Romance; PSYCHOLOGY -- Mental Health; Personal coaching; SELF-HELP -- Personal Growth -- Happiness; Self-actualization (Psychology); Self-actualization (Psychology); Self-care, Health; Self-help techniques; Self-realization; Nonfiction; Self-help publications; Self-help publications; Nonfiction